Efficacy of the novel tubulin polymerization inhibitor PTC‐028 for myelodysplastic syndrome. Issue 12 (2nd November 2020) - Zhong, Cheng; Kayamori, Kensuke; Koide, Shuhei; Shinoda, Daisuke; Oshima, Motohiko; Nakajima‐Takagi, Yaeko; Nagai, Yurie; Mimura, Naoya; Sakaida, Emiko; Yamazaki, Satoshi; Iwano, Satoshi; Miyawaki, Atsushi; et al.
Abstract: Monomer tubulin polymerize into microtubules, which are highly dynamic and play a critical role in mitosis. Therefore, microtubule dynamics are an important target for anticancer drugs. The inhibition of tubulin polymerization or depolymerization was previously targeted and exhibited efficacy against solid tumors. The novel small molecule PTC596 directly binds tubulin, inhibits microtubule polymerization, downregulates MCL‐1, and induces p53‐independent apoptosis in acute myeloid leukemia cells. We herein investigated the efficacy of PTC‐028, a structural analog of PTC596, for myelodysplastic syndrome (MDS). PTC‐028 suppressed growth and induced apoptosis in MDS cell lines. The efficacy of PTC028 in primary MDS samples was confirmed using cell proliferation assays. PTC‐028 synergized with hypomethylating agents, such as decitabine and azacitidine, to inhibit growth and induce apoptosis in MDS cells. Mechanistically, a treatment with PTC‐028 induced G2/M arrest followed by apoptotic cell death. We also assessed the efficacy of PTC‐028 in a xenograft mouse model of MDS using the MDS cell line, MDS‐L, and the AkaBLI bioluminescence imaging system, which is composed of AkaLumine‐HCl and Akaluc. PTC‐028 prolonged the survival of mice in xenograft models. The present results suggest a chemotherapeutic strategy for MDS through the disruption of microtubule dynamics in combination with DNA hypomethylating agents. Abstract : PTC‐028, a novel microtubule polymerization inhibitor, suppresses the growth of MDS cells. PTC‐028 synergizes with DNA hypomethylating agents to inhibit the growth of MDS cells. PTC‐028 prolongs the survival of mice in a xenograft MDS model.